2014
DOI: 10.1080/20445911.2014.941847
|View full text |Cite
|
Sign up to set email alerts
|

Larger, smaller, odd or even? Task-specific effects of optokinetic stimulation on the mental number space

Abstract: Previous studies have shown that number processing can induce spatial biases in perception and action and can trigger the orienting of visuospatial attention. Few studies, however, have investigated how spatial processing and visuospatial attention influences number processing. In the present study, we used the optokinetic stimulation (OKS) technique to trigger eye movements and thus overt orienting of visuospatial attention. Participants were asked to stare at OKS, while performing parity judgements (Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 72 publications
9
35
0
Order By: Relevance
“…Wiemers et al 2014) or by comparing numerical performance under free-viewing conditions versus inhibited viewing conditions. Inhibition of free viewing can, for example, be achieved by instructing participants to fixate a static object, by temporarily paralyzing eye muscle, or by inducing involuntary eye movements through optokinetic (e.g., Ranzini et al 2014) or caloric (e.g., Ferrè et al 2013) vestibular stimulation. Impaired numerical performance in incongruent or inhibited eye movement conditions would suggest a role of the eyes as ''slave'' system for the mind that ''spatializes'' abstract thoughts to support understanding and manipulation of its contents.…”
Section: Discussionmentioning
confidence: 99%
“…Wiemers et al 2014) or by comparing numerical performance under free-viewing conditions versus inhibited viewing conditions. Inhibition of free viewing can, for example, be achieved by instructing participants to fixate a static object, by temporarily paralyzing eye muscle, or by inducing involuntary eye movements through optokinetic (e.g., Ranzini et al 2014) or caloric (e.g., Ferrè et al 2013) vestibular stimulation. Impaired numerical performance in incongruent or inhibited eye movement conditions would suggest a role of the eyes as ''slave'' system for the mind that ''spatializes'' abstract thoughts to support understanding and manipulation of its contents.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings provide the first demonstration that the allocation of numerical magnitude can be differentially modulated by the perceptual state of self that is experienced during visual but not vestibular‐mediated motion. Notably, our experimental design controlled for both any task‐associated variability (Priftis et al ., ) or eye movement‐related effects (Ranzini et al ., ) upon numerical processing.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in normal healthy individuals, a recent study has demonstrated that rightward visual motion can abolish the classical number size effect during a number comparison task (i.e. faster reaction times for small than large numbers) (Ranzini et al ., ). In contrast, Salillas et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…One instance of such overlap-based interaction occurs between the size (volume) of an afforded hand grip and the size (magnitude) of a numerical concept. Indeed, several studies confirmed that participant respond faster when the perceived object’s size corresponds to the perceived number’s magnitude (e.g., Andres et al, 2004, 2008; Lindemann et al, 2007; Moretto and Di Pellegrino, 2008; Ranzini et al, 2011, Gianelli et al, 2012; Namdar et al, 2014; Ranzini et al, 2015; van Dijck et al, 2015). These findings have been extended in other studies to include overlap between non-manipulable object size and numbers (Gabay et al, 2013), weight and numbers (Holmes and Lourenco, 2013), and sound volume and numbers (Heinemann et al, 2013).…”
Section: Representational Overlap: Interactions Between Partially Relmentioning
confidence: 92%